Anomie and Religiosity: An Empirical Re-Examination - Carr, Leslie G. (Journal for the scientific study of religion, 1976)
The hypothesis that religiosity reduces anomie in modern society is re-examined. Anomie was not found to be inversely related to religiosity. An inverse relationship between anomie and class was not reduced by religiosity. Controls for acquiescent and social desirability measurement error did not alter this finding nor did the substitution of an alternative measure of anomie.